PERAN KOMUNITAS BELAJAR DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SMPN 2 CIWIDEY - Henita; Nandang Rusmana; Maulia Depriya Kembara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Pedagogical competence is one of the essential abilities of teachers in managing student-centered learning in accordance with Law Number 14 of 2005 concerning Teachers and Lecturers and Director General Regulation Number 2626/B/HK.04.01/2023. Increasing pedagogical competence can be achieved through various means, one of which is learning communities. This research aims to explore the role of learning communities in improving the pedagogical competence of teachers at SMP Negeri 2 Ciwidey. The research was conducted on 4-8 November 2024 using descriptive qualitative methods through surveys and interviews with teachers who actively participate in the learning community at SMPN 2 Ciwidey. This research maps all research samples into levels of pedagogical competency. The research results show that learning communities have a significant influence on increasing teacher pedagogical competence. Three levels of pedagogical competency for SMPN 2 Ciwidey teachers were obtained, namely 16% of teachers were at level 3, 69% of teachers were at level 4 and 14% of teachers reached level 5. Research recommends a continuous professional development program for teachers at level 3 through intensive training and strategic collaboration . Teachers at levels 4 and 5 are expected to provide guidance to colleagues through a mentoring program.